Solar energy desalination technology - Zheng, Hongfei (Amsterdam Elsevier, 2017)
Solar Energy Desalination Technology explains how to obtain clean water from sea water using solar energy. Special methods and types used in solar desalination are introduced, providing new thoughts, concepts, and feasible solutions in the desalination field, along with the thermal and economic efficiency relating to current technology. Many places in the world are suffering from fresh water shortage. However, those places are often rich with solar resources, sea water, and/or brackish water resources that could dramatically benefit from solar energy as a viable solution for the production of fresh water.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Saline water conversion; Electronic books